2011
DOI: 10.1098/rspb.2011.1888
|View full text |Cite
|
Sign up to set email alerts
|

The sophisticated visual system of a tiny Cambrian crustacean: analysis of a stalked fossil compound eye

Abstract: Fossilized compound eyes from the Cambrian, isolated and three-dimensionally preserved, provide remarkable insights into the lifestyle and habitat of their owners. The tiny stalked compound eyes described here probably possessed too few facets to form a proper image, but they represent a sophisticated system for detecting moving objects. The eyes are preserved as almost solid, mace-shaped blocks of phosphate, in which the original positions of the rhabdoms in one specimen are retained as deep cavities. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Ever since the "Orsten" fossils were first discovered, they offered new insights into Cambrian life, including the anatomy of early arthropods (e.g., Müller 1979aMüller , b, 1983Müller , 1985Müller & Waloszek 1985, 1987Waloszek 1993, Waloszek & Müller 1990, 1998aMaas et al 2003;Ahlberg et al 2005;Waloszek et al 2007;Haug et al 2009Haug et al , 2010aSchoenemann et al 2012). "Orsten" fossils, originally isolated from upper Cambrian limestone concretions collected in southern Sweden, have now been found worldwide (Maas et al 2006).…”
Section: Fossil Compound Eyesmentioning
confidence: 99%
“…Ever since the "Orsten" fossils were first discovered, they offered new insights into Cambrian life, including the anatomy of early arthropods (e.g., Müller 1979aMüller , b, 1983Müller , 1985Müller & Waloszek 1985, 1987Waloszek 1993, Waloszek & Müller 1990, 1998aMaas et al 2003;Ahlberg et al 2005;Waloszek et al 2007;Haug et al 2009Haug et al , 2010aSchoenemann et al 2012). "Orsten" fossils, originally isolated from upper Cambrian limestone concretions collected in southern Sweden, have now been found worldwide (Maas et al 2006).…”
Section: Fossil Compound Eyesmentioning
confidence: 99%
“…Except for the optical system, as in the calcified lenses of trilobite and ostracod arthropods, other parts of the visual system are not usually preserved in the fossil record, because the soft tissue of the eye and the brain decay rapidly after death, such as within 64 days and 11 days, respectively 7 . Only five studies have reported a fossilized visual receptor [8][9][10][11] or a mould equivalent 12 , all of which involved arthropod eyes. The lack of receptor preservation in fossilized vertebrate eyes has limited their comparison with the eyes of extant relatives.…”
mentioning
confidence: 99%
“…1AB2) (compare ref. 21, Fig 1C). In the ‘cyclopic’ forms such as Cambropachycope clarksoni Walossek and Müller 1990 it is even probable for example to show, that probably polarized light was used for predation, an astonishing convergence with the tactics used by living predatory waterfleas 22 .…”
mentioning
confidence: 88%